USE OF PSYCHOLOGICAL LABORATORY STRESSORS IN STUDYING THE PSYCHOPHYSIOLOGICAL STRESS RESPONSE - Moya- Albiol, Luis; Salvador, Alicia (Anales de Psicología / Annals of Psychology, 2001)
Laboratory tasks are much employed in studying the psychophysiological responses to stress. High reactivity to this type of task has been associated with the onset and development of cardiovascular illnesses. The purpose of this study was to review the main laboratory stressors which have been used in studying the psychophysiological response to stress. Public speaking tasks, arithmetic tasks, the Stroop test, and reaction time tasks among others have been analysed. The effect of these tasks on several psychophysiological variables as well as the comparison of some of the tasks have also been discussed. The response to psychological laboratory tasks are hypertonic, due to the fact that they elicit a moderate increase in the cardiovascular response and an augment in the peripheric resistance. On the contrary, responses to acute physical exercise are hypokinetic with a marked increase in the cardiovascular response and a diminution in the peripheric resistance.